Development of primers amplifying DNA barcoding genes matK and rbcL of Legundi (Vitex trifolia) - Hartanto, Nadhifah Riski; Sari , Banuwati Kartika; Rahayu, Triasuti; Munawaroh , Rima; Fawwaz , Muammar; Purwono , Bambang; Zulperi, Dzarifah; Prayitno, Trio Ageng; Sidiq, Yasir (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Legundi (Vitex trifolia) is one of the crucial ethno-pharmacological plants. However, the genetic exploration of these plants in Indonesia remains limited. Moreover, a set of primers can be an initial important step to explore the genetics of V. trifolia as well as to molecularly identify the species of Legundi. This study aimed to develop the two pairs of primers of maturase-K (matK) and ribulose bisphosphate carboxylase large subunit (rbcL) genes. This type of research is exploratory research using a quantitative approach. The research sampling are the leaves of the V. trifolia species, which were collected from Makassar, Indonesia, and the purposive sampling method. The data were obtained through DNA barcoding, and the data were analyzed using bioinformatics analysis. This study found two pairs of developed primers, matK and rbcL, successfully amplified both matK and rbcL target genes of V. trifolia. The newly developed species-specific primers successfully amplified the matK and rbcL genes of V. trifolia, and sequence analysis revealed high similarity values in BLAST and BOLD databases ranging from 99.2 to 100%, with PCR amplification of the matK marker showing particularly high DNA concentration and specificity for species-level identification. This study supports the genetic exploration and identification of useful ethno-pharmacy plants, V. trifolia. The conclusion of the study shows that two primer pairs of maturase-K (matK) and ribulose bisphosphate carboxylase large subunit (rbcL) genes have been developed from V. trifolia plants. This study supports the genetic exploration and identification of ethnopharmaceutical plants of V. trifolia and the role of bioinformatics tools in molecular studies of medicinal plants.